Impact mathematics : (Clencoe/McGraw-Hill, 2000)
IMPACT Mathematics: Algebra and More, Course 3 is part of an exciting 3-course program developed in cooperation with Education Development Center, Inc. It makes mathematics accessible to more of your students. They spend less time reviewing topics from previous grades and more time progressing carefully and successfully toward the completion of Algebra 1 by the end of grade 8. Informal-to-formal concept development ensures that students build necessary skills and develop conceptual understanding.